Índice de masa corporal y estrés académico en los adolescentes de la Unidad Educativa del Milenio Bernardo Valdivieso, período 2022 – 2023 - Ramón Miranda, Karen Nicole (2024)
Body mass index (BMI) in adolescents can be affected by various situations, one of them being the academic stress to which they are exposed daily. The purpose of this research was to identify the BMI, to know the stressors, symptoms and coping strategies in the face of academic stress and to establish the relationship between the degree of body mass index and the level of academic stress in adolescents of the Bernardo Valdivieso Millennium Educational Unit, period 2022 - 2023. With a quantitative, descriptive, prospective, and cross-sectional cohort approach, made up of 270 students, to whom the BMI was calculated and the questionnaire Systemic Cognitive Inventory for the study of academic stress SV-21 was applied, where 49.6% were represented by the female sex and 50.3% by the male sex, in terms of age, 53.6% correspond to the first stage from 10 to 14 years old and 46.2% to the age group from 15 to 19 years old. The results show that 50% have a normal weight, predominantly males between 15 and 19 years of age with 16.30% and 12.96% in females between 15 and 19 years of age. Regarding the level of academic stress, 44.81% showed a mild level of stress, predominantly in the female group, aged 10 to 14 years with 14.07%, followed by 12.59% in males aged 15 to 19 years. When relating the two variables, a value of p = 0.16087766 was obtained, which indicates that there is no statistically significant relationship between the body mass index and the level of academic stress. We conclude that academic stress does not always influence the body mass index of adolescents